Phytophoric Names in Karakalpak Anthroponymy (Texas Journal of Philology, Culture and History, 2022)
The study of personal proper names in the Karakalpak language, the study of their nature and essence, formation and origin, structural and semantic organization, region of distribution, development, improvement of orthoepic and spelling norms is the main problem facing anthroponymy. Proper names, which make up an extensive part of the lexical fund of a particular language, are a kind of historical categories. In this article, for the first time, an attempt is made to describe phytophoric proper names, where plants are identified with the moment of birth and death, are symbols of human life. Personal names preserve and bring to future generations information about a certain stage in the development of human history. Therefore, the study of the problem of phytophoric names in Turkish anthroponymy is of particular relevance.